Primary Omental Lipoma in a Child: A Case Report and Literature Review - Yuan, Qiang; Duan, Xufei; Yan, Xueqiang (Frontiers in Pediatrics, 2022)
Background Lipoma is a common benign tumor derived from adipose tissue, with an incidence of nearly 10%. It is the most common mesenchymal tumor throughout the body. However, the pathogenesis of lipoma is not clear yet, and the increased incidence is attributable to obesity, elevated serum cholesterol, diabetes, trauma, radiation, familial predisposition, and chromosome. Primary omental tumor is a rare lipoma occurring in the greater omentum, most of which is reported in the form of clinical case reports. Nevertheless, primary omental tumor is even rarer in children. To date, there have been few reports of clinical cases. Case Presentation We report a rare case of primary omental lipoma in a 6-year-old boy. After an accidental fall, a CT scan found that he had a tumor in the left upper abdomen. He had no history of abdominal pain, abdominal mass, vomiting, etc. The boy was admitted to the hospital within 3 days, and was diagnosed with an intra-abdominal tumor. After admission, abdominal ultrasound and enhanced CT showed a 71 ×40 ×60 mm mass in the left middle abdomen, which was considered a lipoma. There was no abnormality in tumor markers. Through laparoscopic surgery, intraoperative exploration revealed that the tumor was located in the left mid-upper abdomen, and was yellow, solid, soft, and isolated. The intraoperative diagnosis was an omental lipoma. We used an ultrasonic knife to resect the omentum close to the base of the tumor. The tumor was completely resected, put in a retrieval bag and sealed. Finally, the left and right sides of the umbilical incision were extended to take out the tumor tissue. The child received liquid food 6 h after the operation and was discharged 3 days later. The postoperative pathological diagnosis was an omental lipoma. He was seen at follow-up 3 months after discharge and had no complaints, an abnominal ultrasound showed no tumor recurrence. Conclusion Primary omental lipoma in children is a rare benign tumor of the omentum. Its etiology and pathology are not clear. US, CT, and MRI can facilitate clinical diagnosis and preoperative evaluation. Laparoscopic surgery is an effective treatment, and the prognosis of children is favorable. This case is beneficial to improve the clinical knowledge of pediatric surgeons about this rare disease.